Doping-dependent optoelectronic, and magnetic properties of monolayer SnS. (December 2022) - Asghar, Mazia; Ullah, Hamid; Iqbal, M. Waqas; Shin, Young-Han
Abstract: Based on the first-principles calculations, we examine the effects of In/Sb/P doping on the structure, electronics, and magnetic properties of monolayer SnS. We have examined that the In-/Sb-/P-doped SnS is energetically more favorable under the S-rich condition due to high formation energies. The doping of In at Sn site keeps the semiconducting nature of monolayer SnS, and the Sb doping turns it to metallic. Interestingly, the In-doping turns the non-magnetic monolayer SnS to the magnetic one with a magnetic moment of 1.00 μ B . Additionally, the ferromagnetic behavior is observed at a larger distance confirming the large range ferromagnetism in the In-doped SnS. Importantly, for the In-doped system, a high MAE of 40.91 meV is calculated. Furthermore, the doping P at the S-site in monolayer SnS trun the semiconductor nature to a metallic one. Additional experimental studies into the efficient utilization of these systems in the fields of photo-electronics and magnetic semiconductor devices are very desirable.